The Higher Accounting Education in Primorsky Territory: History and New Horizons of Development - Olga G. Zhitlukhina; Oksana S. Temchenko; Svetlana Yu. Rakutko (Учёт. Анализ. Аудит)
This article is devoted to the history of development of the higher accounting education in Primorsky Territory: starting from the creation of the Vladivostok branch of the Moscow institute of a national economy of G.V. Plekhanov and up to the creation of the joint chair of accounting, the analysis and auditing of the School of Economics and Management of the Far Eastern Federal University. The article considers how the purposes of educational programs changed through the years depending on the requirements of the economy, and which tasks are defined for the perspective. The article states historical milestones of the development of the accounting chair, since 1964 and until present, the formations of scientific and pedagogical faculties during this period, when the first head of that chair was Ivan Fyodorovich Machnev, an outstanding scientist and organizer. The authors paid special attention to the perspectives of implementation of the new educational programs for the bachelor degree and master degree, which were developed by the chair according to the educational standards that are independently set by the Far Eastern Federal University, and are oriented at modern business community requests and recommendations of the International Federation of Accountants in the field of accounting education and the experience of implementation of similar programs at leading universities of Asian-Pacific region.